What Happens in Criminal Firms after Godfather Management Removal? Judicial Administration and Firms Performance - Francesca M. Calamunci (Global Labor Organization (GLO), 2020)
In this paper, I assess the causal effects of judicial administration on a sample of Italian criminal firms in the period 2004-2016, to shed light on the dynamic path of the firm's performance from pre-seizure to the post-entry judicial administration phase. By using exogenous enforcement law decisions imposed by authorities for each case, I estimate their impact, highlighting the economic consequences of having new legal governance aiming to establish legality and the perpetuation of activities. The results show that there are adverse effects on profitability and efficiency with an increase in the leverage level. The empirical evidence shows how organised crime firms are intrinsically managed by their dark criminal side; removing the criminal ties makes it challenging to maintain profitability and efficiency. Overall, the negative results are due to difficulty in establishing a new economic framework for (ex-criminal) firms in which they are able to operate efficiently and according to market rules. ****** Please cite the published version: Calamunci, F.M. (2021), "What happens in criminal firms after godfather management removal? Judicial administration and firms' performance", Small Business Economics. https://doi.org/10.1007/s11187-020-00439-4 ******
Additional information: Please cite the published version: Calamunci, F.M. (2021), "What happens in criminal firms after godfather management removal? Judicial administration and firms' performance", Small Business Economics. https://doi.org/10.1007/s11187-020-00439-4
Keywords: D22; K42; G38; 330; Organised crime; Enforcement Law; Firm level data; Panel data analysis